The major ion chemistry of seawater was closely coupled to the long-term carbon cycle during the Cenozoic - David Evans; Yair Rosenthal; Jonathan Erez; Hagar Hauzer; Laura J. Cotton; Xiaoli Zhou; Romi Nambiar; Peter Stassen; Paul N. Pearson; Willem Renema; Pratul Kumar Saraswati; Jonathan A. Todd; et al. (Proceedings of the National Academy of Sciences, 2026)
A ~fivefold decrease in the atmospheric concentration of CO 2 took place during the Cenozoic. This has often been viewed within the context of silicate weathering changes, although the specific contributions of the potential drivers remain poorly understood. Indeed, it has been alternatively argued that changes in the sea floor spreading rate contributed to the Cenozoic p CO 2 decline, although the magnitude of the decrease means that this is unlikely to account for the entirety of the p CO 2 change. One previously overlooked factor is the concomitant change in the major element composition of seawater, especially the concentration of calcium ([Ca 2+ sw ]), which is typically viewed as responding to processes such as weathering, rather than representing a driver in and of itself. Here, we present the first detailed record of the Cenozoic major ion chemistry of seawater and show that [Ca 2+ sw ] has the potential to control key processes that impact the carbon cycle. Although our record cannot determine whether CO 2 is causally driven by [Ca 2+ sw ], carbon cycle box modeling identifies that this may have been the case. Whether or not [Ca 2+ sw ] indeed directly drove p CO 2 during the Cenozoic principally depends on the strength of the silicate weathering feedback and the magnitude of any possible changes in organic carbon burial, both of which could overwhelm a [Ca 2+ sw ]-driven impact on the carbon cycle. As such, determining the sensitivity of the weathering–climate relationship on million-year timescales is key to resolving whether factors such as seawater major ion composition are important carbon cycle drivers.